2022
DOI: 10.3390/agronomy12092181
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Vegetation Indices to Assess Water and Nitrogen Status of Sweet Maize Crop

Abstract: The deployment of novel technologies in the field of precision farming has risen to the top of global agendas in response to the impact of climate change and the possible shortage of resources such as water and fertilizers. The present research addresses the performance of water and nitrogen-sensitive narrow-band vegetation indices to evaluate the response of sweet maize (Zea mays var. saccharata L.) to different irrigation and nitrogen regimes. The experiment was carried out in Valenzano, Bari (Southern Italy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 94 publications
(98 reference statements)
1
11
0
Order By: Relevance
“…The potential use of the red-edge region for assessing sweet maize nutritional status was confirmed by a study conducted by [45], who reported that the vegetation indices (NDRE, MTCI and CI red-edge ), calculated by red-edge wavelengths, were significantly affected by nitrogen levels. As in our study, they pointed out a positive correlation between the red-edge-based VIs and leaf-gas-exchange parameters.…”
Section: Rgb and Hyperspectral Vegetation Indices For Estimating Maiz...mentioning
confidence: 84%
See 1 more Smart Citation
“…The potential use of the red-edge region for assessing sweet maize nutritional status was confirmed by a study conducted by [45], who reported that the vegetation indices (NDRE, MTCI and CI red-edge ), calculated by red-edge wavelengths, were significantly affected by nitrogen levels. As in our study, they pointed out a positive correlation between the red-edge-based VIs and leaf-gas-exchange parameters.…”
Section: Rgb and Hyperspectral Vegetation Indices For Estimating Maiz...mentioning
confidence: 84%
“…There is evidence from the literature about the high number of studies concerning the use of spectral indices to independently evaluate nitrogen and water status of crops, utilizing either RGB or hyperspectral indices [20,39,45]. However, to the best of our knowledge, none of these studies have specifically addressed the assessment of maize crop response under varied water and nitrogen conditions by integrating both sensing techniques simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [11], vegetation indices were also used to assess the water and nitrogen status of sweet maize. Most of the previous studies were designed using vegetation indices derived from hyperspectral or multispectral data.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it was ensured that each plot had four grid cell values which amounts to 12 values per treatment, per sensing date (4 grid cell x 3 plots per treatment) (Figure 3). The experiment was set up following the procedure already applied for maize in Colovic and Yuand [56] and Piscitelli and Colovicand [57].…”
Section: Experimental Design and On-field Measurementsmentioning
confidence: 99%